1988
DOI: 10.3949/ccjm.55.6.542
|View full text |Cite
|
Sign up to set email alerts
|

Malignant vasovagal syncope: prolonged asystole provoked by head-up tilt: Case report and review of diagnosis, pathophysiology, and therapy

Abstract: is a common clinical disorder that often escapes diagnosis; if the syncope is recurrent and severe (malignant vasovagal syncope), it can be a source of morbidity and possibly mortality. The authors report a 39-year-old patient with recurrent, unexplained syncope who underwent provocative head-up tilt testing that resulted in asystole for 73 seconds. In addition to vasovagal syncope, head-up tilt test also aids in the diagnosis and management of disorders of blood pressure and heart rate regulation. Management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Asystole is associated with syncopal events 50% of the time [4] and may be especially concerning in the perioperative setting; however, no specific definition (eg, duration) of asystole exists [8]. Studies using the controlled environment of tilt table testing have shown that the length of asystole associated with syncope varies from three to 34 seconds [9][10][11][12][13][14][15][16]. However, despite considerable study of VVS, its pathophysiology remains to be fully elucidated [1].…”
Section: Introductionmentioning
confidence: 99%
“…Asystole is associated with syncopal events 50% of the time [4] and may be especially concerning in the perioperative setting; however, no specific definition (eg, duration) of asystole exists [8]. Studies using the controlled environment of tilt table testing have shown that the length of asystole associated with syncope varies from three to 34 seconds [9][10][11][12][13][14][15][16]. However, despite considerable study of VVS, its pathophysiology remains to be fully elucidated [1].…”
Section: Introductionmentioning
confidence: 99%
“…It may occur at any age and accounts for more than one-third of all causes of syncope [1]. Vasovagal syncope is generally considered a benign condition that does not represent a threat to life or significantly impair quality of life [2], although, occasionally, very prolonged ventricular asystole lasting up to 73 s may occur during vasovagal syncope [3]. In tilt-table studies, asystole of over 3-5 s occurs in 15% of patients, with a range from 4 to 33%.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of asystole of 73 seconds, which was reversed with resuscitation and atropine, without any sequelae after the examination 36 . The pauses usually last less than 30 seconds, but longer pauses are not considered major complications.…”
Section: Macedo Et Al Tilt-test -From the Necessary To The Indispensablementioning
confidence: 99%